2005
DOI: 10.1021/ja042672l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Low-Coordinate Iron(II) Fluoride Complexes and Their Use in the Catalytic Hydrodefluorination of Fluorocarbons

Abstract: Transition metal fluoride complexes are of interest because they are potentially useful in a multitude of catalytic applications, including C-F bond activation and fluorocarbon functionalization. We report the first crystallographically characterized examples of molecular iron(II) fluorides: [L(Me)Fe(mu-F)]2 (1(2)) and L(tBu)FeF (2) (L = bulky beta-diketiminate). These complexes react with donor molecules (L'), yielding trigonal-pyramidal complexes L(R)FeF(L'). The fluoride ligand is activated by the Lewis aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
245
3
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(262 citation statements)
references
References 72 publications
9
245
3
4
Order By: Relevance
“…Holland and coworkers have shown that β-dikeminato iron (II) fluoride complexes catalyse HDF of perfluoroaromatics and perflluoroalkenes in the presence of silanes [16]. In particular, HDF of pentafluoropyridine selectively affords the para-substituted product as the only HDF product, although high catalyst loadings are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Holland and coworkers have shown that β-dikeminato iron (II) fluoride complexes catalyse HDF of perfluoroaromatics and perflluoroalkenes in the presence of silanes [16]. In particular, HDF of pentafluoropyridine selectively affords the para-substituted product as the only HDF product, although high catalyst loadings are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Using these ligands, we have isolated the only examples of iron-hydride complexes with a coordination number less than fiVe ( Figure 2). 20,21 Our studies on low-coordinate iron are complemented by those of Peters and co-workers, who use tridentate, strong-field tris(phosphino)borate (BP 3 ) supporting ligands that contain "soft" phosphine donors, and more often give low-spin electronic configurations. 22 In the BP 3 systems, it has not yet been possible to isolate a low-coordinate iron hydride, but the presence of a terminal hydride in four-coordinate complexes is strongly Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Both complexes have roughly tetrahedral geometry at each iron atom. 20,21 implied by the isolation of products that result from activation of solvent or the supporting ligand. 23 Bridging hydrides have recently been observed in a few electronically unsaturated dinuclear complexes, 24,25 and borohydrides have been studied on iron-sulfur clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Der Zustand S = 3/2 ist dagegen verboten, weil die Paarung des vierten und fünften Elektrons in den t 2g -Orbitalen entweder für beide Elektronen gleichermaßen gün-stig (S = 1/2) oder ungünstig ist (S = 5/ 2), aber nicht für das eine Elektron günstig sein kann und für das andere nicht (wie es ein Grundzustand mit S = 3/2 erfordern würde). Beim Tetraeder (T-ML 4 ) scheiden die beiden Spinzustände S = 3/2 und S = 1/2 aus, weil die Energiedifferenz zwischen den e-und t 2 [28,29] (1-3, Abbildung 8), z. B. ein Tripyrazolylborat (E = N), [30] Triphosphanborat (E = P), [31,32] Trithioborat (E = S) [33] oder Tris-(carben)borat.…”
Section: High-spin-und Low-spinkonfigurationenunclassified